M (2-x-y-z) Zn (2-x-y-z) NxYbyTmzO3 nano photo-thermal material and preparation and application thereof
By developing M(2-x-y-z)Zn(2-x-y-z)NxYbyTmzO3 nanophotothermal material and adjusting its chemical composition and preparation process, the problem of difficult to regulate the photothermal performance of lanthanide ion doped nanoparticles in the prior art is solved, and excellent near-infrared luminescence and heating effects are achieved.
Patent Information
- Application Number
- CN202510296351.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-13
AI Technical Summary
The prior art is difficult to achieve upconversion or downconversion emission color fine-tuning of lanthanide ion-doped fluorescent nanoparticles over a wide spectral range, and lacks technology to regulate near-infrared emission and photothermal characteristics.
A new M(2-x-y-z)Zn(2-x-y-z)NxYbyTmzO3 nanophotothermal material was developed. By adjusting the ratio of M, N, x, y, and z, combined with solvent heat treatment technology, the grains and crystal phases of the material are optimized, thereby achieving excellent near-infrared luminescence and heating performance.
It achieves photothermal performance optimization over a wide spectral range, has excellent infrared luminescence and heating characteristics, and is suitable for photoluminescence and/or photothermal applications.
Smart Images

Figure CN119823758A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of functional nanomaterials, and in particular to the field of photothermal multifunctional material technology. Background Art
[0002] Lanthanide ion-doped fluorescent nanoparticles can be used in bioimaging, photovoltaic technology, optical nanothermometers and anti-counterfeiting, and have received widespread attention. So far, a variety of strategies have been developed to regulate the luminescence color, fluorescence lifetime, absolute luminescence intensity and relative intensity of each fluorescence peak of lanthanide ion-doped fluorescent nanoparticles, such as antenna effect, fluorescence resonance energy transfer, cross-relaxation process control, surface effect, energy transfer mediation process, etc.
[0003] Since lanthanide ion-doped fluorescent nanoparticles usually exhibit multi-peak emission spectra, the challenge is to achieve fine-tuning of up-conversion or down-conversion emission colors over a wide spectral range, as well as single-band emission with selected chromaticity. Recently, near-infrared second-band luminescence observed in fluoride nanocrystals doped with Yb3+, Er3+, and Tm3+ has brought new opportunities for bioimaging applications, allowing imaging of deep biological tissues. However, the exploration of color output control of UCNPs cannot ignore the study of novel matrix materials and their manipulation, which depends on the matrix properties and the luminescent dopant concentration.
[0004] In the past few years, oxide materials have attracted great attention due to their low toxicity, excellent optical properties and stability, and promising properties for a wide range of applications, such as LED phosphors, photocatalysts, fuel cells, multiferroics, pressure sensors, topological insulators, and biology. The wide bandgap tunability of oxide materials is used in electronic and energy applications, but there is little existing technology on using this property to manipulate near-infrared emission and simultaneously tune its photothermal properties. Summary of the invention
[0005] The first object of the present invention is to provide a new (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material aims to provide a new material with excellent luminescence and heat generation properties.
[0006] The second object of the present invention is to provide the M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z Preparation method of O3 nano-photothermal material and its application in photothermal material.
[0007] A kind of M(2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material, wherein M is a first main group metal element, N is a rare earth metal element, x is 0.5-1.78, y is 0.05-0.25, z is 0.001-0.03; and the sum of x+y+z is less than 2.
[0008] The present invention provides a nano-photothermal material with a completely new chemical formula, and the new material unexpectedly has an excellent near-infrared luminescence effect, and not only that, it also has an excellent heating effect.
[0009] The present invention also shows that the joint optimization control of M, N as well as x, y, and z can help to unexpectedly further achieve synergy and help to further improve its photothermal performance.
[0010] Preferably, the M includes at least one of Li, Na, and K, preferably Na. Studies of the present invention show that using the Na as M has better compatibility with Zn and can further synergistically improve the photothermal performance of the material.
[0011] In the present invention, the N includes at least one of Y, Lu, Gd, La, and Kc, preferably Y. Studies of the present invention show that using Y as N helps to further improve the photothermal performance of the new material.
[0012] Preferably, the x is 1.5-1.78, more preferably 1.64-1.76; the y is 0.15-0.25, more preferably 0.18-0.2; the z is 0.01-0.03, more preferably 0.01-0.02. x+y+z is equal to 1.84-1.96. The present invention shows that the preferred x, y, and z are helpful to further enhance the photothermal performance of the material.
[0013] The present invention also provides a new Na (1.8-x) Zn (1.8-x) Y x Yb 0.19 Tm 0.01 O3 nanomaterial, wherein x is 1.6 to 1.76. The preferred materials of the present invention, sodium (Na) and zinc (Zn), can coordinately regulate the lattice strain and crystal field symmetry, so that the material can exhibit excellent photothermal properties while maintaining efficient infrared luminescence properties.
[0014] The M of the present invention (2-x-y-z) Zn (2-x-y-z) N x Yb y Tmz O3 nano-photothermal material is a cubic nano-single crystal particle with a grain size of 14 to 18 nm.
[0015] The present invention also provides a kind of M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is to heat-treat a mixed raw material including an M source, a Zn source, a N source, a Yb source and a Tm source to obtain the O3 nano-photothermal material.
[0016] In the present invention, the heat treatment method is solid phase heat treatment or solvent heat, preferably solvent heat.
[0017] In the present invention, the solvent thermal step is: mixing the raw material solutions of the M source, Zn source, N source, Yb source, and Tm source and the auxiliary agent solution, then heating to a temperature of 100 to 300° C. for heat preservation solvent thermal, and then separating to obtain the M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal materials;
[0018] The auxiliary agent solution comprises component A, component B and component C; wherein the component A is C 15 ~C 20 Saturated or unsaturated fatty acids; the component B is C 15 ~C 20 An olefin containing 1 to 2 unsaturated bonds; the component C is C 15 ~C 20 Studies have shown that the solvent thermal treatment under the conditions described in the present invention is helpful to optimize the grains and crystal phases of the new material described in the present invention, and is helpful to further enhance the photothermal properties of the material.
[0019] The component A comprises at least one of oleic acid, hexadecenoic acid and eicosenoic acid.
[0020] The component B includes at least one of octadecene, nonadecene, eicosene, octadecene, heptadecene, hexadecene and pentadecene.
[0021] The component C includes at least one of octadecylamine, oleylamine, and hexadecylamine; preferably includes oleylamine and octadecylamine in a volume ratio of 1 to 3:1. The present invention shows that the preferred combination of component C helps to cooperate with other components, helps to optimize the grains and crystal phases of the new material of the present invention, and helps to further enhance the photothermal performance of the material.
[0022] Preferably, in the auxiliary agent solution, the volume ratio of component A, component B and component C is 1-10:1-10:1-10; further, 1:1.5-2:1-1.5.
[0023] The M source includes at least one of sodium hydroxide, NaHCO3, Na2CO3, and CH3COONa.
[0024] Preferably, the Zn source includes at least one of ZnCl2, (CH3COO)2Zn, ZnCO3, Zn(NO3)2, and ZnSO4.
[0025] Preferably, the N source is at least one of chloride, nitrate, sulfate and acetate of N metal.
[0026] Preferably, the Yb source is at least one of ytterbium chloride, ytterbium nitrate, ytterbium acetate and ytterbium trifluoroacetate.
[0027] Preferably, the Tm source is at least one of thulium chloride, thulium nitrate, thulium acetate and thulium trifluoroacetate.
[0028] In the present invention, the raw materials of the M source, Zn source, N source, Yb source and Tm source are mixed with the auxiliary agent solution in the form of a single solution or in the form of a partial mixture or a complete mixture.
[0029] In the present invention, there is no particular requirement for the concentration of total metal elements in the initial mixed solution of solvothermal treatment, and for example, the concentration may be 0.0005 mol / L to 0.5 mol / L, and further may be 0.01 to 0.05 mol / L.
[0030] In the present invention, the solvothermal process can be carried out in a closed container or an open container.
[0031] In the present invention, the solvothermal temperature is 180-240°C; further 200-220°C. The present invention's research shows that the preferred solvothermal temperature is helpful for synergizing with other components, helping to optimize the grains and crystal phases of the new material of the present invention, and helping to further enhance the photothermal performance of the material.
[0032] In the present invention, the holding time at the solvent thermal temperature is 10 to 30 hours, preferably 20 to 30 hours.
[0033] In the present invention, the temperature of the solid phase heat treatment stage can be 400-600° C., and the time can be 20-30 hours.
[0034] The present invention also provides the M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tmz The application of O3 nano-photothermal material is to use it as a photoluminescent and / or photothermal material.
[0035] Beneficial Effects
[0036] The present invention provides a (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material has excellent photothermal properties. For example, it has excellent infrared luminescence and heating properties.
[0037] The present invention also shows that the joint optimization control of M, N as well as x, y, and z can help to unexpectedly further achieve synergy and help to further improve its photothermal performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is the infrared photoheating spectrum of Example 1.
[0039] Figure 2 This is the infrared photoheating spectrum of Example 2A group.
[0040] Figure 3 This is the infrared photoheating spectrum of Example 2B group.
[0041] Figure 4 This is the infrared photoheating spectrum of Example 3A group.
[0042] Figure 5 This is the infrared photoheating spectrum of Example 3B group.
[0043] Figure 6 This is the infrared photoheating spectrum of Example 3C group.
[0044] Figure 7 This is the infrared photoheating spectrum of Example 4A group.
[0045] Figure 8 This is the infrared photoheating spectrum of Example 4B group.
[0046] Fig. 9 This is the infrared photoheating spectrum of Example 5.
[0047] Fig.10 This is the infrared photoheating spectrum of Comparative Example 1.
[0048] Fig.11 This is the infrared photoheating spectrum of Comparative Example 2.
[0049] Fig.12 This is the infrared photoheating spectrum of Comparative Example 3.
[0050] Fig.13 This is the infrared photoheating spectrum of Comparative Example 4A.
[0051] Fig.14 This is the infrared photoheating spectrum of Comparative Example 4B. DETAILED DESCRIPTION
[0052] In order to better understand the present invention, the content of the present invention is further described below in conjunction with the drawings and embodiments, but the present invention is not limited to the following examples.
[0053] The M of the present invention (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material can be obtained by heat treating a mixed raw material including an M source, a Zn source, a N source, a Yb source, and a Tm source.
[0054] For example, an optional oxide Na of the present invention (1.8-x) Zn (1.8-x) Y x Yb 0.19 Tm 0.01 The preparation method of O3 photothermal dual-function nanomaterial comprises the following steps:
[0055] 1) Add oleic acid, octadecene, oleylamine and octadecylamine into a three-necked flask, and heat and stir to form a uniform solvent;
[0056] 2) dropping aqueous solutions of sodium hydroxide, ytterbium chloride, yttrium chloride, thulium chloride and zinc acetate into the solvent obtained in step 1) in sequence;
[0057] 3) heating and stirring the solution obtained in step 2) to uniformly obtain;
[0058] 4) transferring the emulsion obtained in step 3) into a reaction kettle and reacting it under sealed conditions;
[0059] 5) The reaction product obtained in step 4) is naturally cooled to room temperature, and then subjected to processes such as centrifugal separation, washing, and vacuum drying to obtain the oxide Na (1.8-x) Zn (1.8-x) Y x Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0060] In an optional scheme of the present invention, in step 1), the volume ratio of oleic acid, octadecene, oleylamine and octadecylamine is 25:45:20:10.
[0061] In an optional solution of the present invention, the reaction temperature in step 3) is 180-240° C. and the reaction time is 10-30 h;
[0062] In an optional solution of the present invention, the heating rate of step 3) is controlled at 3-5°C per minute, the purpose of which is to allow the solvent in the reaction container to form a solvent system that is as uniform as possible before the reaction temperature reaches 180-240°C.
[0063] In an optional solution of the present invention, in step 5), the vacuum drying temperature is 50-65° C. and the drying time is 20-40 hours.
[0064] Example 1
[0065] Step 1: add oleic acid, octadecene, oleylamine and octadecylamine in a volume ratio of 25:45:20:10 into a three-necked flask, and heat and stir to form a uniform solvent;
[0066] Step 2: dripping aqueous solutions of sodium hydroxide (M source), zinc chloride, yttrium chloride (N source), ytterbium chloride and thulium chloride into the solvent obtained in step 1) in the molar ratio of metal elements Na, Zn, Y, Yb, Tm=0.04:0.04:1.76:0.19:0.01 in sequence;
[0067] Step 3: Heat and stir the solution obtained in step 2) to obtain an emulsion (the concentration of the metal element in the mixed emulsion is 0.01 mol / L);
[0068] Step 4: The emulsion obtained in step 3) is transferred into a reaction kettle and kept reacting at 210°C for 24 hours under sealed conditions;
[0069] Step 5: The reaction product obtained in step 4) is naturally cooled to room temperature, and then subjected to processes such as centrifugal separation, washing, and vacuum drying to obtain the oxide Na 0.04 Zn 0.04 Y 1.76 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0070] The photothermal test performance of the material is shown in Figure 1 The wavelength of the irradiated laser is 980 nanometers, and the power density is 1.0 watts per square millimeter. After continuous irradiation for 10 seconds, the temperature of the photothermal material rises from 24°C to 41.1°C, indicating that it has good infrared and photothermal properties.
[0071] Example 2
[0072] Compared with Example 1, the only difference is that the M source is changed, and the experimental groups are:
[0073] A source: M source is LiOH, and finally Li0.04 Zn 0.04 Y 1.76 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0074] B source: M source is KOH, and K 0.04 Zn 0.04 Y 1.76 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0075] The test was carried out according to the method of Example 1, and the results were:
[0076] Group A: The photothermal test results of Group A in Example 2 are shown in Figure 2 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 37.6°C.
[0077] Group B: The photothermal test results of Group B in Example 2 are shown in Figure 3 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 39.7°C.
[0078] It can be seen from Examples 1 and 2 that M=Na can achieve synergistic composition and lattice adaptation, which can unexpectedly further improve its photothermal performance.
[0079] Example 3
[0080] Compared with Example 1, the only difference is that the N source (N oxide) is changed. The experimental groups are:
[0081] A source: N source is Gd, and finally Li is obtained 0.04 Zn 0.04 G 1.76 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0082] B source: N source is Lu, and finally Li is obtained 0.04 Zn 0.04 Lu 1.76 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0083] C source: N source is La, and finally Li is obtained 0.04 Zn 0.04 La 1.76 Yb 0.19Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0084] The test was carried out according to the method of Example 1, and the results were:
[0085] Group A: The photothermal test results of Group A in Example 3 are shown in Figure 4 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 38.2°C.
[0086] Group B: The photothermal test results of Group B in Example 3 are shown in Figure 5 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 38.6°C.
[0087] Group C: The photothermal test results of Group C in Example 3 are shown in Figure 6 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 38.9°C.
[0088] It can be seen from Examples 1 and 3 that N=Y can achieve synergistic composition and lattice adaptation, which can unexpectedly further improve its photothermal performance.
[0089] Example 4
[0090] Compared with Example 1, the only difference is that the ratio of the elements in step 2 is changed, and the experimental groups are:
[0091] Group A: Na, Zn, Y, Yb, Tm = 0.1: 0.1: 1.7: 0.19: 0.01, finally Na 0.1 Zn 0.1 Y 1.7 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0092] Group B: Na, Zn, Y, Yb, Tm = 0.16: 0.16: 1.64: 0.19: 0.01; Na 0.16 Zn 0.16 Y 1.64 Yb 0.19 Tm 0.01 O3 photothermal dual-functional nanocrystalline powder.
[0093] The test was carried out according to the method of Example 1, and the results were:
[0094] Group A: The photothermal test results of Group A in Example 4 are shown in Figure 7The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 watts per square millimeter. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 41.9°C.
[0095] Group B Example 4 The photothermal test results of Group B are shown in Figure 8 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 41.3°C.
[0096] Example 5
[0097] Compared with Example 1, the only difference is that the solvent thermal reaction is not carried out, but the metal raw materials in step 2 are mixed in the solid state and then directly solid-phase calcined in air at 500°C for 24 hours to obtain the product. The photothermal test results are shown in Fig. 9 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After continuous irradiation for 10 seconds, the temperature of the photothermal material increased from 24°C to 34°C.
[0098] It can be seen from Examples 1 and 5 that the solvothermal reaction described in the present invention can further enhance the phase and grain control of the new material, which helps to further enhance the photothermal performance of the prepared material.
[0099] Example 6
[0100] Compared with Example 1, the only difference is that the solvent in step 1 is oleic acid, octadecene, oleylamine and octadecylamine in a volume ratio of 25:45:30; other operations and parameters are as in Example 1. The test results are: the irradiation laser wavelength is 980 nanometers, the power density is 1.0 watts per square millimeter. After continuous irradiation for 10 seconds, the temperature of the photothermal material rises from 24°C to 38.4°C.
[0101] It can be seen from Examples 1 and 6 that the use of the quaternary solvent for solvent thermal treatment helps to further strengthen the lattice and grain control of the new material described in the present invention, and helps to further improve the photothermal performance of the material.
[0102] Example 7
[0103] Compared with Example 1, the only difference is that in step 1, the solvent is oleic acid, eicosene and oleylamine in a volume ratio of 1:1.5:1; the metal solution in step 2 is controlled to 0.02M; the temperature in step 4 is 190°C and the time is 28h. Other operations and parameters are the same as in Example 1. The test results are: the irradiation laser wavelength is 980 nanometers and the power density is 1.0 watts / square millimeter. After continuous irradiation for 10 seconds, the temperature of the photothermal material rises from 24°C to 37.8°C.
[0104] Comparative Example 1
[0105] Compared with Example 1, the only difference is that in step 2, the Na source and the zinc source are missing, and in step 2, the ratio of Y, Yb, and Tm is 1.8:0.19:0.01, and the other operations and parameters are the same as in Example 1. Finally, Y 1.8 Yb 0.19 Tm 0.01 O3 nanocrystalline powder.
[0106] The results of the photothermal test are shown in Fig.10 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 watts per square millimeter. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 32.1°C.
[0107] Comparative Example 2
[0108] Compared with Example 1, the only difference is that zinc is lacking, and the missing charge is supplemented by Na, and the final material is Na 0.12 Y 1.76 Yb 0.19 Tm 0.01 O3.
[0109] The results of the photothermal test of Comparative Example 2 are shown in Fig.11 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 31.8°C.
[0110] Comparative Example 3
[0111] Compared with Example 1, the only difference is that Na is missing, and the missing charge is supplemented by Zn, and the final material is Zn 0.06 Y 1.76 Yb 0.19 Tm 0.01 O3. The photothermal test results of comparative example 3 are shown in Fig.12 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 watts per square millimeter. After continuous irradiation for 10 seconds, the temperature of the photothermal material increased from 24°C to 31.5°C.
[0112] Comparative Example 4
[0113] Compared with Example 1, the only difference is that other divalent elements are used to replace Zn in equal molar amounts. Other operations and parameters are the same as those in Example 1. The experimental groups are:
[0114] Group A: The zinc chloride was replaced by an equal molar amount of calcium chloride;
[0115] Group B: manganese chloride was used in an equal molar amount to replace the zinc chloride;
[0116] The tests are:
[0117] Group A: Photothermal test results are shown in Fig.13 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 30.2°C.
[0118] Group B: Photothermal test results are shown in Fig.14 The wavelength of the irradiated laser was 980 nanometers and the power density was 1.0 W / mm2. After 10 seconds of continuous irradiation, the temperature of the photothermal material increased from 24°C to 30.7°C.
Claims
1. A M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material, characterized in that: The M is a first main group metal element, the N is a rare earth metal element, the x is 0.5-1.78, the y is 0.05-0.25, the z is 0.001-0.03; and the sum of the x+y+z is less than 2.
2. The M according to claim 1 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material, characterized in that: The M includes at least one of Li, Na and K.
3. The M according to claim 1 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material, characterized in that: The N includes at least one of Y, Lu, Gd, La, and Kc.
4. The M according to any one of claims 1 to 3 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material, characterized in that: The x is 1.5-1.78, the y is 0.15-0.25, and the z is 0.01-0.
03.
5. A M according to any one of claims 1 to 4 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is characterized in that: The mixed raw material including an M source, a Zn source, a N source, a Yb source and a Tm source is heat-treated to obtain the obtained source.
6. The M according to claim 5 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is characterized by: The heat treatment method is solid phase heat treatment or solvent heat.
7. The M according to claim 6 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is characterized in that: The solvent thermal step is: mixing the raw material solutions of the M source, Zn source, N source, Yb source, and Tm source and the auxiliary agent solution, then heating to a temperature of 100 to 300° C. for heat preservation solvent thermal, and then separating to obtain the M (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal materials; The auxiliary agent solution comprises component A, component B and component C; wherein the component A is C 15 ~C 20 Saturated or unsaturated fatty acids; the component B is C 15 ~C 20 An olefin containing 1 to 2 unsaturated bonds; the component C is C 15 ~C 20 Saturated or unsaturated primary amines; In the auxiliary agent solution, the volume ratio of component A, component B and component C is 1-10:1-10:1-10.
8. The M according to claim 7 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is characterized by: The M source includes at least one of sodium hydroxide, NaHCO3, Na2CO3, and CH3COONa; The Zn source includes at least one of ZnCl2, (CH3COO)2Zn, ZnCO3, Zn(NO3)2, and ZnSO4; The N source is at least one of chloride, nitrate, sulfate and acetate of N metal; The Yb source is at least one of ytterbium chloride, ytterbium nitrate, ytterbium acetate and ytterbium trifluoroacetate; The Tm source is at least one of thulium chloride, thulium nitrate, thulium acetate and thulium trifluoroacetate; The concentration of total metal elements in the initial mixed solution of solvothermal reaction is 0.0005 mol / L~0.5 mol / L.
9. The M according to any one of claims 6 to 8 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The preparation method of O3 nano-photothermal material is characterized in that: Solvothermal temperature is 180~240℃; The holding time at the solvent thermal temperature is 10~30h.
10. The M according to any one of claims 1 to 4 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z O3 nano-photothermal material or M prepared by the preparation method according to any one of claims 5 to 9 (2-x-y-z) Zn (2-x-y-z) N x Yb y Tm z The application of O3 nano-photothermal material is characterized by: It is used as a photoluminescent and / or photothermal material.
Citation Information
Patent Citations
Fluoride photo-thermal difunctional nano material and preparation method thereof
CN114106831A
Near-infrared emission silver nanocluster / polymer composite material with photothermal conversion performance and preparation method thereof
CN116254105A
Preparation of solar photo-thermal conversion material with strong near-infrared light absorption and application of solar photo-thermal conversion material in degradation of organic pollutants
CN119349693A